Mandatory Grievance in Iraqi Legislation: A Comparative Study - Abdul-Ridha Abdul-Khaliq, Researcher. Jaafar (Basra studies journal, 2025)
The administration possesses mechanisms through which it fulfills public needs, including administrative decisions. Although the administration is committed to applying the law when issuing its administrative decisions, individuals may question their validity, prompting them to object. The Iraqi legislator has provided a formal mechanism for objection, known as grievance, which is mandatory. Despite its advantages, this mechanism poses certain challenges. Many cases are dismissed by administrative courts due to individuals’ failure to file a grievance, the limited period for submitting grievances, the absence of a clearly designated authority to review grievances, and the formal requirements governing the process. This study concludes that the mandatory grievance should be retained, with improvements: extending the grievance submission period from 30 to 60 days and specifying the authority responsible for reviewing the grievance explicitly within the administrative decision.